2006
DOI: 10.1093/mutage/gel023
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, anticlastogenic and radioprotective effect of Coleus aromaticus on Chinese hamster fibroblast cells (V79) exposed to gamma radiation

Abstract: Coleus aromaticus (Benth, Family: Laminaceae), Indian Oregano native to India and Mediterranean, is well known for its medicinal properties. A preliminary study was undertaken to elucidate in vitro free radical scavenging potential and inhibition of lipid peroxidation by C.aromaticus hydroalcoholic extract (CAE). Anti-clastogenic and radioprotective potential of CAE were studied using micronucleus assay after irradiating Chinese hamster fibroblast (V79) cells. CAE at 10, 20, 40, 60, 80, 100 and 120 mug/ml resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 30 publications
1
29
0
2
Order By: Relevance
“…[378] It may be therefore logical to expect that extracts and bioactive compounds with antioxidant potential derived from plants may render radioprotection to normal tissues as evidenced from earlier reports. [79101112131415]…”
Section: Introductionmentioning
confidence: 99%
“…[378] It may be therefore logical to expect that extracts and bioactive compounds with antioxidant potential derived from plants may render radioprotection to normal tissues as evidenced from earlier reports. [79101112131415]…”
Section: Introductionmentioning
confidence: 99%
“…(Family: Laminaceae), is an important medicinal plant used widely to treated a number of illness (Lans et al, 2007;Pritima and Pandian, 2007) and has been reported to protect liver and other disorders in rats (Choudhary, 2009;Vijayavel et al, 2013). The antioxidant potential of this plant was investigated in various standard in vitro free radical generating model systems that included DPPH, 2,2-azinobis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS), O 2 •-, ˙OH and nitric oxide (NO) (Rao et al, 2006). Different concentrations (10-120 μg/ml) of hydroalcoholic extract of C aromaticus (CAE) showed concentration-dependent increase in radical scavenging ability against various free radicals.…”
Section: Coleus Aromaticusmentioning
confidence: 99%
“…In vitro studies with cancer cell lines, showed that oregano extract protect against oxidative stress and DNA damage from radiation (Rao et al, 2006;Bakkali et al, 2006). Additionally, oregano extract was found to have strong antioxidant activity, through the capture free radicals, suppression of fat oxidation, inhibition of NOS and protection of DNA from H 2 O 2 -induced oxidative damage (Zheng & Wang, 2001;Aherne et al, 2007;Tsai et al, 2007).…”
Section: Mediterranean Herbs and Cancer Chemopreventionmentioning
confidence: 99%